2013
DOI: 10.1080/08870446.2013.845668
|View full text |Cite
|
Sign up to set email alerts
|

How appropriate is the WHOQOL-BREF for assessing the quality of life of adolescents?

Abstract: The evidence indicates that developing a new adolescent version is justifiable. Cross-cultural research should build on these preliminary findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 30 publications
3
16
0
2
Order By: Relevance
“…This is consistent with the unique social and emotional aspects for different age groups [31,64,65]. It is advocated that adolescent outcome measures should address the importance of separation from parents [31,66]. However, few adolescents in this study selected and rated independence from parents highly.…”
Section: Results In Context With Previous Literaturesupporting
confidence: 75%
See 2 more Smart Citations
“…This is consistent with the unique social and emotional aspects for different age groups [31,64,65]. It is advocated that adolescent outcome measures should address the importance of separation from parents [31,66]. However, few adolescents in this study selected and rated independence from parents highly.…”
Section: Results In Context With Previous Literaturesupporting
confidence: 75%
“…This study also demonstrated the different activities important to different age groups as well as older adolescents worrying more about the future. This is consistent with the unique social and emotional aspects for different age groups [31,64,65]. It is advocated that adolescent outcome measures should address the importance of separation from parents [31,66].…”
Section: Results In Context With Previous Literaturesupporting
confidence: 68%
See 1 more Smart Citation
“…Similarly, the appropriateness of the World Health Organization Quality of Life (WHOQOL-BREF) for use among youth has been questioned, as its development was almost based on adults or adult patients, and discussions about its applicability and/or validation in children and adolescents are scarce ( 18 ). Some authors have called for the development of a new adolescent version of the WHOQOL ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Del mismo modo, cuando mencionamos el término calidad de vida (CV) de un paciente, comprendemos esta idea como la discrepancia entre la expectativa y su realidad; en otras palabras, cuanto mayor sea la desigualdad entre los mencionados, menor será su CV (3) . Asimismo, la calidad de vida relacionada con la salud (CVRS), la cual es multidimensional, predomina por la interrelación de factores individuales, sociales y ambientales (4) , y claramente diferenciable por parte del paciente de la percepción del estado de salud (5) . Participan aspectos en relación con al menos tres componentes: uno individual (relacionado con el estrés que supone la enfermedad para el paciente), uno de interacción (que tiene que ver con el apoyo social) y otro comunitario (relacionado con un sentido de pertenencia) (6,7) .…”
Section: Cambios Hemodinámicos Y Calidad De Vida En Pacientes Con Cánunclassified